Hacia una economía circular en el sector forestal - Villegas Vega, Paul (2025)
The purpose of this paper is to examine the favorable contribution of circular economy implementation in the use of forestry resources. To achieve this, the study begins by reviewing the current regulation and status of forest resources, then analyzes the application of the circular economy as a proposal that contributes to the vision of sustainable development and finally assesses the impact that the circular economy may have on the forestry sector, considering the challenges that such implementation would entail.